The nowhere firm: Pandemic lessons for all businesses from startups born office-less. (Economist, 2020)
The article focuses on the impact of the Coronavirus on the distributed companies. It mentions that most firms that build blockchains, a type of distributed database, are by their nature dispersed; and firms offering organisational scaffolding for distributed firms include Rippling, that manages payroll and employee benefits.